From supportive galenic compounding to advanced clinical pharmacy: A decade of excellence and safety in the Antiblastic Drugs Unit in Southern Italy (2014–2025) - Filomena D'Amico; Rosa Moscogiuri; Loredana Brandi; Francesco Colasuonno; Mariangela Calcagno; Alessandro Maggi; Claudia Ingrosso; Tiziana Guarino; Antonio Ungaro; Vito Gregorio Colacicco; Salvatore Pisconti (Journal of Oncology Pharmacy Practice, 2026)
Objectives Antiblastic Drugs Units (ADUs) ensure safety, appropriateness and sustainability of oncology treatments. Over the last decade, hospital pharmacists have expanded their role from aseptic compounding to advanced clinical pharmacy. This study describes the ten-year evolution of the ADU of ASL Taranto in Southern Italy, focusing on clinical, organisational and strategic value generated from 2014 to 2025. Methods A retrospective descriptive analysis of activity data, organisational changes and clinical pharmacy services was conducted. Key indicators include compounded preparations, quality systems, technological innovations, service centralisation, CAR-T therapy management, clinical trials, compassionate use programmes and COVID-19 emergency response. Results Between March and December 2014, 17,508 antiblastic preparations were compounded (daily average: 83). Activity increased to 53,300 in 2025 (daily average: 212), representing a 204% increase. The ADU achieved and maintained ISO 9001:2015 certification since 2017. Since 2022, 49 CAR-T therapies were managed, including quality assurance and AIFA registry monitoring. The ADU evolved into a Clinical Trial Centre, supporting six phase II-III trials in 2025, and enabled access to innovative medicines through compassionate use programmes (62 patients in 2025). During COVID-19, the unit served as central hub for vaccine and remdesivir management. Despite a 1194% increase in pharmaceutical expenditure (€2.54 M to €32.87 M), systematic reimbursement management generated €8.92 M in recoveries and savings in 2025 (27.1% of expenditure). Conclusions The experience of this ADU illustrates how a structured, quality-driven approach can support the transformation of aseptic compounding into advanced clinical pharmacy. The integration of pharmacists into multidisciplinary oncology teams was associated with strengthened medication safety processes, expanded access to innovation and improved economic sustainability, suggesting a potential reference model for comparable settings.